2018
DOI: 10.1515/ap-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with Tritrichomonas foetus infection in cattle in the state of Paraíba, Brazil

Abstract: The objective of this study was to determine the prevalence of Tritrichomonas foetus infection and to evaluate risk factors associated with this infection among cattle in the state of Paraíba in northeastern Brazil. Samples of cervicovaginal mucus from 290 females and smegma from 59 males [beef, 31; mixed aptitude (beef and dairy), 10; and dairy, 18] from 31 farms were collected. Modified Diamond's medium and polymerase chain reaction (PCR) were used for the laboratory diagnosis of T. foetus infection. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…A similar epidemiological situation was observed in certain countries of South America, South Africa, and Asia, and in Australia. The prevalence of tritrichomonosis in Argentina was 3.5% (30) and was 3.7% in Brazil (12) where natural service was the main way of reproduction. A study conducted in Costa Rica showed that 18.4% of cows and 7.2% of bulls had T. foetus infection (42).…”
Section: Bovine Tritrichomonosismentioning
confidence: 99%
“…A similar epidemiological situation was observed in certain countries of South America, South Africa, and Asia, and in Australia. The prevalence of tritrichomonosis in Argentina was 3.5% (30) and was 3.7% in Brazil (12) where natural service was the main way of reproduction. A study conducted in Costa Rica showed that 18.4% of cows and 7.2% of bulls had T. foetus infection (42).…”
Section: Bovine Tritrichomonosismentioning
confidence: 99%
“…Parsonson et al [48] reported that the mating of a bull infected with T. foetus with 20 susceptible multiparous cows resulted in 19 (95%) animals becoming infected after a single service. De Oliveira Filho [24] described factors that might contribute to the initiation or dissemination of infection, such as herds sharing livestock with other owners or farmers, greater bull-to-cow ratio, presence of old bulls in the herd, extensive management setting, and absence of disease information.…”
Section: Discussionmentioning
confidence: 99%
“…BT, an endemic disease in most countries with extensive cattle ranching with natural service as a reproductive method (Rae et al, 2004;Mardones et al, 2008;Filho et al, 2018), is one of the main causes of reproductive failure and generates large economic losses (Honigberg et al, 1971;Felleisen, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Bovine trichomoniasis (BT), a sexually transmitted disease is widely distributed throughout the world, is endemic to most countries with extensive cattle farming with natural service as a reproductive method (Rae et al, 2004;Mardones et al, 2008;Filho et al, 2018). BT is one of the most common causes of reproductive failure, which translates into an increase in the calving interval and embryo death, resulting in a marked decrease in the pregnancy rate of a cattle herd with great economic losses (Honigberg et al, 1971;Felleisen, 1999).…”
mentioning
confidence: 99%